Hubungan Antara Perilaku Overprotective Orang Tua Terhadap Perkembangan Psikologis Pada Anak Usia Dini - Ardhea Rizka Mumtadzah; Deni Febrini; Fatrica Syafri (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2021)
This study aims to determine the relationship between parental overprotective behavior on psychological development in early childhood in Arkarami housing, Sukarami Village, Selebar District, Bengkulu City. The method used in this research is quantitative. Collecting data using a questionnaire technique. Data analysis using quantitative analysis techniques. The results showed that the calculated r was 0.690 > r table at df = 28 was 0.374, so it can be concluded that the X and Y variables have a significant relationship. Thus, the hypothesis (Ha) which reads that there is a significant relationship between parents' overprotective behavior on psychological development in early childhood in Arkarami Housing, Sukarami Sub-district, Selebar District, Bengkulu City is proven and acceptable. Keywords: Overprotective behavior, early childhood psychology parents. References Apriliani, F. T., & Nurwati, N. (2020). Pengaruh Perkawinan Muda terhadap Ketahanan Keluarga. Prosiding Penelitian Dan Pengabdian Kepada Masyarakat, 7(1). https://doi.org/10.24198/jppm.v7i1.28141 Damayanti, E., & Nasrul, M. A. (2020). Capaian Perkembangan Fisik Motorik Dan Stimulasinya Pada Anak Usia 3-4 Tahun. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 5(2), 67–80. Emzir. (2015). Metodologi Penelitian Pendidikan Kuantitatif & Kualitatif,. Rajawali Pers. Harlina, D., Novitasari, V., Sari, M. N., A.m, R. A., & Rianti, E. (2017). Sikap Over Protective Orangtua Terhadap Perkembangan Anak. JPGI (Jurnal Penelitian Guru Indonesia), 2(2), 1–8. https://doi.org/10.29210/02218jpgi0005 Imroatun, I., Nirmala, I., Juhri, J., & Muqdamien, B. (2020). Kajian Literatur Pengasuhan Anak Usia Dini Dalam Islam. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 5(1), 57–66. Mashar, R. (2011). Emosi Anak Usia Dini Dan Strategi Pengembangannya. Prenada Media Group. Maya S. (2020). Psikologi Perkembangan Anak Memaksimalkan Pertumbuhan Dan Kemampuan Buah Hati. C-Klik Media. Munandar, U. (2009). Pengembangan Kreativitas Anak Berbakat. Rineka Cipta. Nurhayati, R. (2019). Membangun Budaya Literasi Anak Usia Dini dalam Keluarga. Nuansa Akademik: Jurnal Pembangunan Masyarakat, 4(1), 79–88. https://doi.org/10.47200/JNAJPM.V4I1.918 Nuryati, N., & Yuniawati, N. (2019). Peningkatan Kreativitas Pada Anak Usia Dini Kelas SD Awal Usia 6-8 Tahun Melalui Metode Praktikum Membatik. As-Sibyan : Jurnal Pendidikan Anak Usia Dini, 4(1), 1–12. Pohan, J. E. (2020). Pendidikan Anak Usia Dini (PAUD) Konsep Dan Perkembangan. Rajawali Pers. Porter, A. (2020). Segala Sesuatu Yang Perlu Anda Ketahui Tentang Psikologi. Gramedia Pustaka Utama. Sari, S. Y. (2017). Tinjauan Perkembangan Psikologi Manusia pada Usia Kanak-Kanak dan Remaja. PRIMARY EDUCATION JOURNAL (PEJ), 1(1), 46–50. Sri Lestari. (2013). Psikologi Keluarga. Kencana. Sugiyono. (2013). Metode Penelitian Pendidikan (Pendekatan Kuantitatif, Kualitatif dan R&D). Alfabeta. Syafri, F. (2018). MEMAHAMI PERKEMBANGAN PSIKOLOGI KEAGAMAAN ANAK USIA DINI. Al Fitrah: Journal Of Early Childhood Islamic Education, 2(1), 242–250. https://doi.org/10.29300/alfitrah.v2i1.1519 Umayah, U. (2017). Perkembangan Sosial Pada Anak Usia Dini. As-Sibyan : Jurnal Pendidikan Anak Usia Dini, 2(1), 85–96. https://doi.org/10.1017/CBO9781107415324.004 Wiyani, N. A. (2014). Psikologi Perkembangan Anak Usia Dini Panduan Bagi Orang Tua Dan Pendidik Paud Dalam Memahami Serta Mendidik Anak Usia Dini. Gava Media.